Characteristics of the dependences of mobility and concentration of charge carriers in monocrystals CdSb(In) after γ-irradiation - Fedosov, A.V.; Koval, Y.V.; Jashchinskij, L.V.; Kovalchuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The results of researches of the kinetic effects in crystals CdSb are presented and discussed.